Reframing Environmental Accounting Through Indigenous-Based Asset Valuation and Socio-Ecological Integration - Kurniawan Patma; Maria Yosephine Dwi Hayu Agustini; Ignasius Dwi Atmana Sutapa (International Journal of Applied Business and International Management, 2026)
Conventional environmental accounting practices still have significant limitations because they mainly emphasize monetary valuation while neglecting the socio-cultural and ecological dimensions embedded in indigenous asset systems. This research aims to develop an indigenous-based asset valuation and environmental accounting model that integrates economic, ecological, and socio-cultural values within indigenous community enterprises. This study employs a mixed-methods approach using Participatory Action Research (PAR), combining qualitative techniques (in-depth interviews, participatory observation, and collective reflection) with quantitative valuation based on the Total Economic Value (TEV) framework. The findings reveal that indigenous assets are perceived as collective socio-ecological trusts, where non-use values, especially existence and bequest values, are central alongside direct and indirect use values. The study proposes an indigenous-based environmental accounting model that generates ecological financial statements covering natural resource assets, social and environmental liabilities, and non-financial reports. This model has practical implications for improving accountability, sustainability, and policy formulation in indigenous economic governance, but it is context-specific and requires adaptation for broader application in different indigenous settings.